MULTICULTURALISM IN HINDU RELIGIOUS EDUCATION PERSPECTIVE - Subrahmaniam Saitya, Ida Bagus; Suastika Arimbawa, I Komang; Gaduh, Acyutananda Wayan; Suryanti, Putu Emy; Rahayu, Ni Putu Ersa (Institut Hindu Dharma Negeri Denpasar, 2020)
Indonesia, like other developing countries, has social problems that are not simple. The economic crisis followed by various other crises made people aware of the importance of social capital. Social capital is the collective energy of the community in the form of togetherness, solidarity, cooperation, tolerance, trust, and responsibility of every society members in playing their duties and obligations. The development of dynamic society and social problems that continue to develop these days, require attention and sensitivity from all nation elements, not only from experts and observers of social problems but also the education world, especially concerning religious education which has a very strategic role as a vehicle and ?agent of change? for the society. The pluralistic condition of Indonesia both in terms of ethnicity, race, religion, and social status makes an extraordinary contribution to the development and dynamics in society. Therefore, it is considered very important to provide a portion of religious education in a multicultural perspective in the Indonesian education system, both through substance and learning models. This is considered important to provide a briefing and foster the development of insight and personality, also train students' sensitivity in facing the social symptoms and problems that occur in society.